Regulatory roles of circular RNAs in poultry diseases: mechanisms and research advances - Sumayya; Rudayni, Hassan A.; Shuaib, Muhammad; Li, Bichun; Sun, Hongyan; Ullah, Obaid; Alawam, Abdullah S.; Allam, Ahmed A.; Elolimy, Ahmed A.; Abd El-Hack, Mohamed E. (Frontiers in Veterinary Science, 2025)
Research on circular RNA (circRNA) in poultry increasingly explores its role as a potential regulator in various diseases. It has also shown differential expression of circRNAs in infected tissues, signifying their participation in disease pathogenesis and immune response mechanisms. Additionally, it can function as microRNA sponges, blocking the binding of microRNAs to their target mRNAs and modifying the expression of specific genes. circRNAs are being explored as potential biomarkers for early disease detection and monitoring of disease progression. They are highly expressed and stable in various chicken tissues, offering new insights into their role in tumor development. circRNAs are also being researched as a tool for gene editing, where they could potentially be utilized to increase or repress particular genes in therapeutic contexts. The vast quantity of circRNAs with unknown functions in the eukaryotic transcriptome means that, despite recent progress, our knowledge of the crucial role of circRNAs in viral infections and antiviral immune responses is still unclear. circRNA is a viable contender as a biomarker for bacterial infections due to its stability and distinct expression patterns. Numerous viral disorders have been found to exhibit altered circRNA expression profiles, suggesting their potential use in disease diagnostics. This review briefly introduces the biogenesis, characteristics, and functions of circRNAs, focusing on their progress in research on poultry diseases.